Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Karyawan dan ASN Pada Dinas Tenaga Kerja,Transmigrasi dan Kependudukan Provinsi Nusa Tenggara Timur - Andrias Umbu Tuku Anabuni; Cornelia Amelia Thonak (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The aim of this research is to obtain empirical evidence of how much influence transformational leadership and work motivation simultaneously and partially have on the performance of employees and ASN at the Manpower, Transmigration and Population Service of East Nusa Tenggara Province.The population in this study was ASN from the Manpower, Transmigration and Population Service of East Nusa Tenggara Province, totaling 248 employees. The sample obtained was 153 people, using the Proportional Random Sampling technique. The variables in this research are transformational leadership and work motivation as independent variables and employee performance as the dependent variable. Data collection methods were carried out by means of observation, documentation and questionnaires. The data analysis method used is descriptive percentage, multiple linear regression analysis method, simultaneous test, partial test. The results of data regression analysis show the following equation Y=0.301+0.728 X1 + 0.513 Simultaneously (leadership and motivation) have a significant effect on employee performance by 61.5%. Meanwhile, the remaining 38.5% is influenced by other factors.It was concluded that the more positive the transformational leadership and work motivation, the higher the employee performance. Suggestions related to the research results are that leaders should be able to maintain good relationships with employees at work, so that employees feel comfortable at work, need to maintain or increase employee motivation at work and plan the training and development programs needed to improve employee performance at work.